A new model of alcoholic fermentation under a byproduct inhibitory effect - Zentou, Hamid; Zainal Abidin, Zurina; Yunus, Robiah; Awang Biak, Dayang Radiah; Issa, Mohammed Abdullah; Pudza, Musa Yahaya (American Chemical Society, 2021)
Despite the advantages of continuous fermentation whereby ethanol is selectively removed from the fermenting broth to reduce the end-product inhibition, this process can concentrate minor secondary products to the point where they become toxic to the yeast. This study aims to develop a new mathematical model do describe the inhibitory effect of byproducts on alcoholic fermentation including glycerol, lactic acid, acetic acid, and succinic acid, which were reported as major byproducts during batch alcoholic fermentation. The accumulation of these byproducts during the different stages of batch fermentation has been quantified. The yields of total byproducts, glycerol, acetic acid, and succinic acid per gram of glucose were 0.0442, 0.023, 0.0155, and 0.0054, respectively. It was found that the concentration of these byproducts linearly increases with the increase in glucose concentration in the range of 25–250 g/L. The results have also showed that byproduct concentration has a significant inhibitory effect on specific growth coefficient (μ) whereas no effect was observed on the half-velocity constant (Ks). A new mathematical model of alcoholic fermentation was developed considering the byproduct inhibitory effect, which showed a good performance and more accuracy compared to the classical Monod model.